Making military conscription count? Converting competencies between the civilian and military spheres in a neoliberal Estonia - Lillemae, Eleri; Ben-Ari, Eyal; Kasearu, Kairi (Current Sociology, 2024)
While past decades Western societies have been shifting from mandatory military service toward all-volunteer forces, a number of them have retained conscription. A growing emphasis on individualization and neoliberalist ideas results in a tension for youths between fulfilling a duty and the need for constant self-development. We argue that a central mechanism for addressing this challenge is convertibility, the ability to use competencies gained in one sphere in another, and thus increasing the individual value of conscription for recruits. By linking convertibility to societal expectations, we demonstrate how societies shape ideas of what is convertible and why, and by relating convertibility to agency and motivation, we extend the concept to the individual level. We argue that as material rewards are limited and conscripts cannot rely on occupational motivations, convertibility has a potential to increase the value of conscription for recruits and enable them to combine institutional motivators with utilitarian motives.
Keywords: Agency; Conscription; Convertibility; Military; Motivation